Modern concept of general paralysis (Bayle´s disease) - Trelles, J. O. (1935)
A short summary made ​​in outline, of the pathology of the disease Bayle seems essential to appreciate at its fair value, the influence of histopathological Malariaterapia formula on this condition. But before going into the same subject let us note the great revival movement that has caused genuine natural therapeutics anatomic this chapter might seem, however, been secured. This movement has brought, thanks to modern methods and broader research orientation, a number of new facts or almost seem such. So so abundant scientific production we see flourish in France, Germany, Italy and the United States are legitimate.